2011
DOI: 10.1523/jneurosci.3363-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Organization of the Taste System in theDrosophilaLarva

Abstract: We examine the molecular and cellular basis of taste perception in the Drosophila larva, through a comprehensive analysis of the expression patterns of all 68 Gustatory receptors (Grs). Gr-GAL4 lines representing each Gr are examined, and 39 show expression in taste organs of the larval head, including the terminal organ (TO), the dorsal organ (DO), and the pharyngeal organs. A receptor-to-neuron map is constructed. The map defines 10 neurons of the TO and DO, and it identifies 28 receptors that map to them. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
245
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(254 citation statements)
references
References 59 publications
8
245
1
Order By: Relevance
“…Expression analysis of the Gr genes using the GAL4-UAS system has shown that 39 of the predicted proteins are likely to be expressed in the TO, DPS, VPS, or PPS of the larva (11,14,15). However, a receptor-to-neuron map of the TO neurons suggested that many TO neurons did not express any Gr genes, consistent with the notion that some larval taste neurons may express other kinds of taste receptors (15).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Expression analysis of the Gr genes using the GAL4-UAS system has shown that 39 of the predicted proteins are likely to be expressed in the TO, DPS, VPS, or PPS of the larva (11,14,15). However, a receptor-to-neuron map of the TO neurons suggested that many TO neurons did not express any Gr genes, consistent with the notion that some larval taste neurons may express other kinds of taste receptors (15).…”
mentioning
confidence: 58%
“…By contrast, drivers of IR67b and IR94f also express in the DPS but extend projections that appear distinct from the projections of IR60e, IR67c, and IR94h. The patterns of these five lines are reminiscent of patterns observed for certain Gr-GAL4 drivers that are expressed in the DPS (15). Projections in the SOG were not detected for IR20a-GAL4, which is expressed in the DPO, or for IR94d-GAL4, which is expressed in the abdomen, nor did we observe projections for IR48c-GAL4, which was examined in the small SOG of the first instar, or IR60b-GAL4, which is a weak driver.…”
Section: Expression Of Ir20a Clade Drivers Is Distributed Among Multiplementioning
confidence: 76%
See 1 more Smart Citation
“…We note that an earlier study observed a repellent effect of geranyl acetate (8); we do not know the basis of this difference, but repellency has been found to be sensitive to larval age (37) and could also be sensitive to other factors that differed between the two studies (38). Aversive responses to CO 2 are mediated by neurons of another larval organ, the terminal organ, that coexpress Gr21a and Gr63a (2,(39)(40)(41)(42), and it is possible that other unidentified neurons also mediate airborne aversive responses.…”
Section: Discussionmentioning
confidence: 82%
“…3H, Right; Movie S4). The cellular expression patterns of all 68 gustatory receptor genes have been systematically characterized (29). None of these expression patterns include neurons that resemble the thermosensory neurons.…”
Section: Resultsmentioning
confidence: 99%